Assessing Code Compliance and Mason Proficiency in Residential Construction in Birendranagar Municipality, Surkhet (OCEM Journal of Management, Technology & Social Sciences, 2025)
Urbanization is rapidly increasing worldwide, and refers to the process by which rural areas transform into urban areas, where cities in Karnali Province are experiencing significant growth. However, much of this expansion is characterized by informal construction, with over 80% of housing lacking compliance with building codes, thereby increasing vulnerability to disasters like the 2015 Gorkha Earthquake and the 2023 Jajarkot Earthquake. This study evaluates building code compliance in residential RCC buildings within Birendranagar Municipality, focusing on both completed and underconstruction buildings. The research adopts a qualitative approach, combining literature review, field surveys, and questionnaire administration to gather and analyze data.Key findings reveal that among the 22 completed buildings surveyed, only 5 fully complied with the approved designs, with common issues including noncompliant staircases, beams, and room layouts. For the 22 under-construction buildings, 8 demonstrated full compliance, especially in foundation work, tie beams, and rebar sizing, although non-compliance issues like slab thickness, bar lapping positions, and staircase dimensions were identified. Additionally, 11 out of the 22 completed buildings met municipal bye-laws, especially with regard to ground coverage ratio and building height, but setbacks and floor area ratios were frequently violated. The study also found that most masons lacked formal training, with only 30% aware of earthquake-resistant design principles. Masons relied primarily on practical experience, with limited knowledge of building codes and municipal approval processes. Findings highlight the need for increased training for masons, greater awareness for homeowners, and improved municipal oversight to ensure better compliance and safer construction practices.